A hitherto unknown stability of DNA basepairs. Issue 93 (5th November 2020) - Davis, Daly; Sajeev, Y.
Abstract : The resonance capture of very low energy electrons (vLEEs) into the π* orbitals of nucleobases is a potential doorway to DNA damage. A rapid nonenzymatic structural response specific to the complementary basepairing is found to prevent direct damages. Abstract : The resonance capture of ubiquitous very low energy electrons (vLEEs) into the π* orbitals of nucleobases is a potential doorway to DNA damage. Our ab initio quantum chemical calculations reveal a possible protection function, which is specific to the complementary basepairing, against such vLEE induced DNA damage.